The Global COVID-19 Student Survey: First Wave Results - David A. Jaeger; Jaime Arellano-Bover; Krzysztof Karbownik; Marta Martínez Matute; John M. Nunley; Jr. Seals; Miguel Almunia; Mackenzie Alston; Sascha O. Becker; Pilar Beneito; René Böheim; José E. Boscá; et al. (Institute of Labor Economics (IZA), 2021)
University students have been particularly affected by the COVID-19 pandemic. We present results from the first wave of the Global COVID-19 Student Survey, which was administered at 28 universities in the United States, Spain, Australia, Sweden, Austria, Italy, and Mexico between April and October 2020. The survey addresses contemporaneous outcomes and future expectations regarding three fundamental aspects of students' lives in the pandemic: the labor market, education, and health. We document the differential responses of students as a function of their country of residence, parental income, gender, and for the US their race.
Keywords: I23; I10; J1; 330; mental health; job market expectations; students; COVID-19